THE DYNAMICS OF MOSQUITOES POPULATION BASED ON RAINFALL AND TEMPERATURE - Seprianus
This thesis discusses how to approximate functions of rainfall and daily mean temperature by using least square method with trigonometry polynomial. Ap- proximation error resulted by this method will be compared to which resulted by Fast Fourier Transform method. The approximation is purposed to accom- modate climatic factors into deterministic model of mosquitoes population. The mathematical model of mosquitoes population used in this thesis is one which discussed in [11]. Analytically, with constant entomological parameters, the model yields two xed points, trivial and non-trivial. The model also yields a quantity named Basic Ospring Number, Q0. The necessary and sucient condition for stability of non-trivial xed point to hold is Q0 > 1. Accommo- dation of functions of rainfall and daily mean temperature into model is done by constructing a carrying-capacity function of time which contains functions of rainfall and daily mean temperature. The numerical simulation shows that behaviors of functions of rainfall and daily mean temperature signicantly im- pact the dynamics of mosquitoes population.